Pengendalian Pembuatan Asphalt Hot Mix Pada Asphalt Mixing Plant Menggunakan PLC - Prasetyo Aziz (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
Asphalt hot mix manufacture consists of mixer and weighing which is a part of the mixing process which is controlled automatically using PLC at the asphalt mixing plant SPECO TSAP-800AS. All processes in the asphalt mixing plant have used computer-based electromechanical automation, especially the application of PLC control on the Mixer and Weighing section, considering that the mixing process must always be stable and run continuously so it must be controlled automatically using a combination of relays and air dampers. The scale sensor used is a load cell which functions to calculate the weight of solid material from hot bin CB1/1 to CB1/5. The mixer used has a capacity of 800 kilogram per batch. The design of controlling the manufacture of asphalt hot mix at the asphalt mixing plant TSAP-800AS was made using Outseal Studio V2.2 software.